Ensino de leitura e escrita em crianças com diferentes necessidades educacionais especiais por meio de um programa informatizado de ensino - Fava Menzori, Letícia Regina [UNESP] (2016)
The computer-based software named Learn to Read and Write in Small Steps (Aprendendo a Ler e a Escrever em Pequenos Passos®) was created based on the methodological proposal subsidized by the paradigm of equivalence relations. The software’s goal is to establish elementary repertoire of reading and writing of different levels of complexity, which efficiency has been replicated in different laboratories. The objective of this research was to verify the effects of this computer-based software on both the reading and writing repertoire of children with different diagnosis of special teaching necessities and verify the answer expense of the participants during the steps of the program. The records of nine seven to 11 year-old children, that had been diagnosed with communication disorders as well as intellectual deficiency, that were regularly enrolled in the Ensino Fundamental I (Elementary School), also attending the resource room, were analyzed. The kids were subjected to the Reading and Writing Net Evaluation that involves reading tasks, reading comprehension, copying and dictation, amongst others along the Módulo de Ensino (Teaching Module) which is composed of 20 steps, each teaching three words. In the pre-evaluation of the Reading and Writing Net the percentage of score was practically null or very low for all the participants. In the post-evaluation, the results of some participants reached 100% of score. Although the necessity of repetition of certain steps has been recorded for some of the participants, seven of them were able to finish the steps of the teaching software. The data inspires investigation of procedures of teaching that minimize the occurrence of mistakes during the learning process of this population.